The gut microbiome and metabolomic alterations underlying colitis-induced encephalopathy in mice: mechanistic insight - Aimin Cai; Dingchao Shen; Qiushuang Xiong; Shize Li; Chenyu Qiu; Lele Li; Zhiwei Chen; Xinlu Lin; Qing Yao; Youting Zhang; Ruijie Chen; Longfa Kou (Behavioral and Brain Functions)
Abstract Background In addition to classical gastrointestinal symptoms, patients with inflammatory bowel disease (IBD) often exhibit neurological manifestations, such as mood disorders and cognitive dysfunctions, which are frequently overlooked. However, the potential pathogenesis of IBD-related encephalopathy remains unclear, and few studies have explored the influence of interactions between the gut microbiota and the host gut-brain metabolome on the emergence of brain diseases in IBD mice. In this study, we conducted a comprehensive analysis of gut microbiome and metabolome alterations in dextran sulfate sodium salt (DSS)-induced IBD mice compared to control mice, focusing on colonic contents and hippocampal tissue. Our aim was to investigate the putative mechanisms underlying the microbiota-gut-brain axis in IBD-induced encephalopathy. Results IBD mice showed depression-like behaviors and cognitive deficits. Metabolic profiling revealed distinct patterns in the colonic contents and hippocampal areas of IBD mice, marked by decreased energy metabolism, amino acid levels, short-chain fatty acids (SCFAs), and choline metabolism. These metabolic changes were negatively associated with the abundance of Bacteroides, Turicibacter, Ruminococcus, and Akkermansia, while Desulfovibrio and Lactobacillus showed positive correlations. Conclusions This study identifies unique microbial and gut-brain metabolite signatures associated with DSS-induced changes and offers new metabolic insights into the microbiota-gut-brain axis in IBD-related brain disorders. It highlights the potential of targeting gut microbiota to modulate host metabolism as a therapeutic approach for IBD-related neurological complications.